Photosynthetic and Growth Responses in a Pioneer Tree (Japanese White Birch) and Competitive Perennial Weeds (Eupatorium sp.) Grown Under Different Regimes With Limited Water Supply to Waterlogging - Kitao, Mitsutoshi; Harayama, Hisanori; Yazaki, Kenichi; Tobita, Hiroyuki; Agathokleous, Evgenios; Furuya, Naoyuki; Hashimoto, Toru (Frontiers in Plant Science, 2022)
For a successful natural regeneration of Japanese white birch (Betula platyphylla var. japonica), competitive vegetation should be managed. Here, we clarified how soil water condition modifies the competitiveness of Japanese white birch against perennial weeds, Eupatorium species, based on an ecophysiological approach combining a glasshouse experiment and a field survey. We investigated photosynthetic and growth responses to various water regimes from water deficit to waterlogging (twice-a-week irrigation, thrice-a-week irrigation, half-waterlogging, and full-waterlogging) in pot-grown seedlings of Japanese white birch and the competitive weed Eupatorium makinoi. The ratio of seedling height of Japanese white birch to seedling height of E. makinoi showed a decreasing trend from twice-a-week irrigation to full-waterlogging, suggesting a lower competitiveness for light resource in Japanese white birch with increasing soil wetness. The maximum rate of Rubisco carboxylation (Vc,max) based on unit N was lower in waterlogging treatments than in twice- and thrice-a-week irrigation in Japanese white birch, whereas E. makinoi showed the opposite response. This suggests that N partitioning into Rubisco and/or Rubisco activation might be suppressed in Japanese white birch but enhanced in E. makinoi under waterlogging. The maximum photochemical efficiency of photosystem II (Fv/Fm) was also lower in seedlings of Japanese white birch grown under waterlogging treatments. We further conducted a field survey on the relationship between Fv/Fm and topographic wetness index (TWI) in seedlings of Japanese white birch and E. glehnii (closely related to E. makinoi) naturally grown in a study site five years after canopy tree cutting. Lower Fv/Fm was observed in seedlings of Japanese white birch with increasing TWI, whereas no significant trend was observed in E. glehnii, in agreement with the glasshouse experiment. Thus, keeping soils not always humid might be favorable to photosynthetic performance and growth competitive ability of Japanese white birch against Eupatorium species.